Floristic composition of different habitats of indochinese silvered langur (Trachypithecus germaini) in the Chua Hang karst in Kien Luong district, Kien Giang province, Vietnam - Thia, Le Hong; Duc, Hoang Minh; Covert, Herbert (Academia Journal of Biology, 2019)
The Indochinese silvered langur (Trachypithecus germaini) is a leaf monkey species that occurs on four karst hills in the Kien Luong District, Kien Giang Province, Vietnam. In this study, the floristic composition of four habitats where the silvered langur were observed feeding was analyzed. These habitats include cliffs, slopes, the peak of the Chua Hang karst and the adjacent mangroves. We identified 185 plant species belonging to 61 families distributing across the habitats, and the silvered langurs fed on 60 plant species of 37 families. Among food plants selected by the silvered langur, 41 plant species were distributed on the cliff, followed by the slope (31 species), the peak (24 species), and the mangroves (4 species). The silvered langurs fed on about 67% of plant species on the cliff. Plant species richness of the slope areas was highest (at D=0.45, D: Simpson index, and d=20.0, d: Margalef index) compared with the other habitats. The floristic composition of the cliff, slope and peak was quite similar to each other, with the similarity index (SI) ranging from 0.47 to 0.56. The results showed that four plant species, Phyllathus reticulatus Poir, Ficus rumphii Blume, Streblus ilicifolia (Kurz.) Corn. and Cayratia trifolia L. were consumed throughout of the year. In summary, present results add important information for conservation of the Indochinese silvered langur in Vietnam.